Draft Annual Plan 2003-2004 Volume-II Andaman and Nicobar Administration - Planning Commission (Planning Commission, 2003)
Early Childhood Care and Education is meant to promote assured access to every child for the fulfillment of the basic needs through the period of his growth and to preparer for his formal schooling. ECCE is expected to provide for a holistic development of the child i.e. social, educational, health, physical, nutritional and psychological needs. The National Programme of Education emphasizes the need for sterling ECCE Centres on priority for the groups who are still out in the mainstream of formal education and envisages that the entire population in the age group 3-6 years should be provided comprehensive ECCE. The ECCE centres will be staffed by local.
Andaman & Nicobar Administration Planning Department